Analysis of the Effect of Population Growth, Human Development Index and Unemployment Rate on Poverty in West Java Province 2017-2020 - Anggi Irmaa Lismana; Hadi Sumarsono (Jurnal Ekonomi Pembangunan, 2022)
Poverty is a significant problem faced by several countries. Several factors causing poverty selected population growth, HDI, and unemployment rate, which are studied to influence poverty in the province of West Java. This study aims to see whether population growth, human development index, and unemployment rate contribute to poverty in West Java province in 2017-2020, using secondary data from the Central Statistics Agency (BPS) website. The assisted panel data regression method was used in this study, administered by the STATA application to process the data. The data processing results in this study indicate that population growth and the human development index negatively affect poverty. In contrast, unemployment has a positive-not significant effect on poverty. Simultaneous test results show that population growth, human development index, and unemployment in poverty in West Java Province from 2017 to 2020